Quality evaluation of surrounding rocks in a mine shaft based on the game gray target model - Guo, Li-Ping; Gu, Xin-Bao (Frontiers in Earth Science, 2024)
Accurate evaluation of surrounding rock quality grade can help guarantee the safety of tunnel design and construction; hence, it has great significance in the construction of mine shafts. Accordingly, the uniaxial saturated compressive strength of the rock block Rc, rock quality index RQD, rock softening coefficient kR, integrity coefficient of the rock mass kv, depth H, unit weight of the rock mass γ, coefficient of quantification of the angle between the principal structural plane and shaft axis k2, and weight of the groundwater k1 are first selected as the indexes of assessment to introduce the game gray target model. Then, the gray target model of the surrounding rocks in a mine shaft project is established. The weight coefficient of each index is next calculated using the combination weighting method based on game theory, and the synthetic target center distance of each sample is determined using the gray target model. Finally, the quality level of the asphalt pavement is determined. The suggested model can be used to mine a small data sample to the maximum extent possible, thereby minimizing the information shortage caused by the small sample to a certain extent, to evaluate the final quality grade of the surrounding rocks quantitatively. Thus, the proposed approach provides a new scheme for the future quality assessments of surrounding rocks.